Breeding in Africa for Africa - International Potato Center (2014)
The final major methods experiment demonstrated that controlled cross breeding is superior to polycross breeding. Sixty varieties comprise the 2nd edition of the Catalogue of Orange Fleshed Sweetpotato for Africa, published in July 2014.